Takotsubo Syndrome in a Patient With a Malignant Tumor of the Kidney - N. V. Rutkovskaya; Y. N. Lazarenko; S. R. Shtin; A. S. Samoylov; A. V. Sotnikov; E. A. Praskurnichy; O. V. Parinov; Y. D. Udalov (Неотложная медицинская помощь, 2020)
RELEVANCE. The increasing availability of invasive methods for assessing the coronary vessels contributes to the growth in the diagnosis of myocardial damage in intact coronary arteries. One of the least studied diseases that mimic the course of myocardial infarction is Takotsubo syndrome, which quite often remains undiagnosed in real clinical practice. The medical and economic significance of this disease is determined by the high risk of developing life-threatening complications and the need to provide emergency specialized medical care.AIM OF STUDY. The paper presents an analytical review of scientific medical literature from the perspective of illustrating modern concepts of the most common risk factors, etiopathogenesis, diagnosis and treatment of Takotsubo syndrome. A clinical observation of a patient with verified secondary Takotsubo syndrome against a malignant neoplasm of the kidney is also presented.CONCLUSIONS. For a detailed understanding of the potential mechanisms for the development of Takotsubo syndrome, determining the most informative methods for its diagnosis, developing effective strategies for providing medical care and criteria for long-term prognosis, further large-scale studies are needed. Raising the level of awareness of doctors about Takotsubo syndrome, in turn, will allow timely detection of this disease, which will improve the prognosis for patients and minimize the economic costs of treatment. The exclusion of the possibility of overdiagnosis will also help determine the true prevalence of this disease.